Measuring sustainability under regime shift uncertainty: A resilience pricing approach - Chuan-Zhong Li; Karl-Göran Mäler (Uppsala University, Department of Economics, 2010)
This paper is concerned with the theory of resilience pricing and sustainability measurement in the presence of risk for regime shift in a dynamic economy-environment system. Following Holling (1973),we consider resilience as the maximal perturbation that the system can absorb without flipping into a qualitatively different state. Using a multisector growth model under uncertainty, we derive the shadow price of resilience that affects the probabilities of the system to flip in the future. We also analyze the role of resilience on sustainability with both ex-ante and ex-post welfare measures.
urn:nbn:se:uu:diva-161801
Keywords: D60; D90; Q50; 330; regime shift; resilience; ecosystem; valuation; inclusive wealth; Umwelt; Nachhaltige Entwicklung; Messung; Wohlfahrtstheorie; Zeitpräferenz; Mehr-Sektoren-Modell